2023
DOI: 10.1007/s11912-023-01417-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Therapy for Malignant Brain Tumors: Does It Still Matter?

Abstract: Purpose of Review To summarize the mechanisms of tumor angiogenesis and resistance to antiangiogenic therapy, and the influence on tumor microenvironment. Recent Findings Several clinical trials have investigated the activity of anti-VEGF monoclonal antibodies and tyrosine kinase inhibitors in glioblastoma, shedding the light on their limitations in terms of disease control and survival. We have outlined the mechanisms of resistance to antiangiogenic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…While the monoclonal VEGF-antibody bevacizumab was approved for recurrent glioblastoma in some countries based on prolonged PFS and clinical benefit, such as the reduction of steroid need and neurological symptoms, it did not prolong OS in several phase 3 clinical trials - both in newly diagnosed and recurrent disease [ 3 , 4 , 11 , 14 ]. Following these disappointing results, different mechanisms of resistance to antiangiogenic therapy have been identified such as compensatory angiogenic signaling or vessel co-option [ 15 ]. Some initiatives set out to identify subgroups potentially deriving an OS benefit from bevacizumab, such as the report from Sandmann and colleagues associating the proneural subtype with increased OS from bevacizumab, which seems counterintuitive as the mesenchymal and not the proneural subtype shows elevated angiogenic markers including VEGF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the monoclonal VEGF-antibody bevacizumab was approved for recurrent glioblastoma in some countries based on prolonged PFS and clinical benefit, such as the reduction of steroid need and neurological symptoms, it did not prolong OS in several phase 3 clinical trials - both in newly diagnosed and recurrent disease [ 3 , 4 , 11 , 14 ]. Following these disappointing results, different mechanisms of resistance to antiangiogenic therapy have been identified such as compensatory angiogenic signaling or vessel co-option [ 15 ]. Some initiatives set out to identify subgroups potentially deriving an OS benefit from bevacizumab, such as the report from Sandmann and colleagues associating the proneural subtype with increased OS from bevacizumab, which seems counterintuitive as the mesenchymal and not the proneural subtype shows elevated angiogenic markers including VEGF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Standard treatment fails to improve glioma patient survival in an efficient way, when combining with anti-angiogenic therapy, the clinical results were still unsatisfactory ( 172 , 173 ). After a period of usage, resistance was shown in anti-angiogenic therapy which develops compensatory pathways to maintain glioma angiogenesis and growth ( 16 , 174 ).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Angiogenesis in glioma and GBM is particularly obvious among all tumors ( 13 , 14 ). Anti-angiogenic therapy by targeting AGFs or their receptors has become a hot topic in the treatment of glioma during the past decades ( 15 , 16 ). This therapy differs from the traditional anti-tumor therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete set of protein kinases (kinome) has emerged as an appealing target for therapeutic strategies for human malignancies ( Fleuren et al, 2016 ). Several studies reported that the tumor progression and therapy resistance are subsequently related to overexpression and mutation of TKs that activate many critical downstream pathways in GBM ( Bolcaen et al, 2021 ; Peller et al, 2023 ). In GBM, certain well-characterized mutated TKs are the epidermal growth factor receptor (EGFR), vascular endothelial growth factor receptor (VEGFR), and platelet-derived growth factor receptor-α (PDGFR-α) ( Fleuren et al, 2016 ; Brar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%